Assessing the Drivers of Successful CSR-Based Mangrove Ecotourism: Evidence from PT Imbang Tata Alam, Malacca Strait - Suherman, Jajang; Pendrian, Okder (Dinasti Publisher, 2025)
This research aims to examine the influence of ecotourism management competency, corporate social responsibility (CSR) strategies, and government policies on the development and sustainability of mangrove ecotourism programs at PT Imbang Tata Alam (ITA) in the Malacca Strait. The respondents consisted of CSR team members and ecotourism managers directly involved in the implementation of these programs. Data were collected through a structured questionnaire distributed via Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results reveal that ecotourism management competency, CSR strategies, and government policies significantly affect the development of mangrove-based ecotourism programs. High managerial competency enhances program effectiveness, while strategic CSR initiatives focusing on environmental and community engagement further accelerate progress. In addition, government policy support in the form of regulations and incentives strengthens program sustainability. The study concludes that stakeholder collaboration and inclusive planning are essential to ensuring long-term ecological, social, and economic benefits of mangrove ecotourism.